Improvement of biomass bottom ash properties by carbonation and pulverisation methods for application in cement-based materials - M. Rosales; L. Ahmed; R. Rodríguez; M. Cabrera; F. Agrela; S. Moreno; J. Rosales; J.L. Díaz-López (Materiales de Construccion)
This study evaluated the viability of biomass bottom ash (BBA) as a supplementary cementitious material (SCM) and sand substitute in cement-based materials. Physical and chemical characterization of BBA from eucalyptus forestry biomass and BBA from olive industry residues was performed. BBA underwent processing through grinding for SCM application and carbonation for sand substitution. Mortar mixtures were prepared with 25% ground BBA replacement for cement and 25% and 50% BBA replacement for sand, both carbonated and non-carbonated. Mechanical behaviour tested through flexure and compressive strength and water absorption at 28 days were assessed. Pulverised BBA enhance compressive strength of mortar compared to a conventional CEM II type cement and Carbonated BBA mortar mixtures improved 28-day compressive strength by 35-55% compared to non-carbonated BBA. BBA from eucalyptus forestry biomass, with pozzolanic activity, exhibited superior strength. The findings support the technical feasibility of BBA in cementitious materials, contingent on adequate processing.